Identification and Characterization of a Cold-Active Phthalate Esters Hydrolase by Screening a Metagenomic Library Derived from Biofilms of a Wastewater Treatment Plant - Jiao, Yiying; Chen, Xu; Wang, Xin; Liao, Xuewei; Xiao, Lin; Miao, Aijun; Wu, Jun; Yang, Liuyan (PLOS ONE, 2013)
A cold-active phthalate esters hydrolase gene (designated dphB) was identified through functional screening of a metagenomic library derived from biofilms of a wastewater treatment plant. The enzyme specifically catalyzed the hydrolysis of dipropyl phthalate, dibutyl phthalate, and dipentyl phthalate to the corresponding monoalkyl phthalate esters at low temperatures. The catalytic triad residues of DphB were proposed to be Ser159, Asp251, and His281.